Implementation of Lesson Study in Improving Creative Thinking and Student Learning Outcomes in Social Sciences Subjects - Zuhroh, Ni’matuz (International Journal of Social Learning (IJSL), 2024)
There is a Japanese teacher professional development model that effectively improves the quality of learning, namely Lesson Study. This research aims to analyze the impact of implementing lesson study on improving creative thinking and student learning outcomes in Social Sciences (IPS) subjects at MTsN Batu City. The research method used is classroom action research (PTK) with a qualitative and quantitative approach. The research subjects were students of class VIII MTsN Batu City. Data was collected through observation, interviews, and learning outcomes tests. The research results show that lesson study significantly improves students' creative thinking abilities and learning outcomes. Qualitative Findings: Observations revealed increased student participation in group discussions and submission of new ideas. Teachers report that collaboration in lesson planning allows them to design more interactive and engaging strategies. Interviews with students showed increased confidence and engagement in exploring social studies concepts. Quantitative Findings: Test results show significant improvements in students' academic achievement. The student's average score on the initial test of 75 increased to 85 on the final test, with the t-test showing that this difference was statistically significant (p < 0.05). This demonstrates that lesson study has increased students' understanding and mastery of social studies material.